An investigation into the effects of fiber architecture on the mechanical behavior of woven preforms. Issue 11 (2nd November 2018) - Safarabadi, Majid; Feiz Mohammadi, Hadi
Abstract: This study attempts to analyze the behavior of different types of woven composite preforms (i.e. plain, twill, and satin) under distinct loading conditions. To this end, fabric elements are modeled using discrete finite element approach. Different loading scenarios such as intra-ply shear, in-plane tension, and simultaneous intra-ply shear and in-plane tension loads are applied to the fabric elements. TexGen software is utilized to develop the geometric model of the fabric elements. Subsequently, the geometric model is exported to ABAQUS FE package and mechanistic analyses are conducted. The FE results reveal that under the same loading conditions, the in-plane tensile stress induced in plain weave elements has the minimum value compared to twill and satin elements. Having said that, the intra-ply shear resistance of the plain element is larger than the other weave types. What's more, the behavior of the fabric elements under simultaneous intra-ply shear and tension loading scenarios are studied that discloses almost the similar response for all weave types.